2007
DOI: 10.1634/stemcells.2006-0839
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Expression Level of Protein Kinase Cε Regulate the Megakaryocytic Differentiation of Human CD34 Cells

Abstract: Protein kinase C (PKC)-mediated intracellular signaling participates in several key steps of hematopoietic cell differentiation. The isoform of PKC has been associated with erythroid differentiation as well as with the early phases of megakaryocytic (MK) lineage commitment. Here, we worked on the hypothesis that PKC expression levels might be modulated during MK differentiation, with a specific role in the early as well as in the late phases of thrombopoiesis. We demonstrate that-at variance with the erythroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 35 publications
7
67
0
Order By: Relevance
“…In agreement with our previous studies in human megakaryocyte coltures, 18 PKCe protein expression increases during the early phases of MK differentiation ( Figure 1A). However, unlike human megakaryopoiesis, mouse PKCe remains highly expressed throughout the entire maturation process, including PLT release (relative densitometric measurements of the samples tested are shown in Figure 1B).…”
Section: Pkc« Levels Are Modulated During Mk Differentiationsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our previous studies in human megakaryocyte coltures, 18 PKCe protein expression increases during the early phases of MK differentiation ( Figure 1A). However, unlike human megakaryopoiesis, mouse PKCe remains highly expressed throughout the entire maturation process, including PLT release (relative densitometric measurements of the samples tested are shown in Figure 1B).…”
Section: Pkc« Levels Are Modulated During Mk Differentiationsupporting
confidence: 93%
“…17 We recently showed that expression of protein kinase Cepsilon (PKCe), a member of the protein kinase C family of serine/ threonine kinases, changes throughout the course of thrombopoietin (TPO)-induced megakaryocyte (MK) differentiation from human CD34 pos cells. 18,19 PKCe has been implicated in both the regulation of cytoskeleton remodeling and the RhoA pathway. 20 Specifically, PKCe, unlike other PKC family members, contains an F-actinbinding region that promotes the formation of F-actin filaments by preventing depolymerization and increasing the rate of actin filament elongation.…”
Section: Introductionmentioning
confidence: 99%
“…The respective sense and antisense RNA sequences of double-stranded small interfering RNA (siRNA), designed to target human PKCε mRNA (siRNA PKCε ), were synthesized by Silencer siRNA Construction Kit (Ambion, Austin, TX) as previously described (32,33). Nonspecific siRNA duplexes containing the same nucleotides, but in irregular sequence (i.e., scrambled PKCε siRNA), were prepared according to manufacturer's protocol and used as controls.…”
Section: Small Interfering Rna Design and Transfectionmentioning
confidence: 99%
“…Fifty mg proteins from each sample were then migrated in 5% SDS-acrylamide gels and blotted onto nitrocellulose filters. Blotted filters were blocked and incubated with specific primary Abs diluted as previously described (32,33). Specifically, rabbit polyclonal anti-PKCε and anti-b-actin Abs were used at the concentration of 1 mg/ml and diluted 1:5000, respectively.…”
Section: Western Blotmentioning
confidence: 99%
“…It is well known that PKCs play an important role in the differentiation of megakaryocytes from cell lines [4][5][6][7][8]. However, the function of specific PKC isoforms, with the exception of " and a, in primary megakaryopoiesis is currently unknown [9][10][11]. A previous report suggests that PKCy mRNA expression is enhanced during megakaryocyte differentiation from progenitor cells, more so than any other PKC isoform [12].…”
mentioning
confidence: 99%